Carbon nanotubes embedding organic ionic plastic crystals electrolytes for high performance solid-state dye-sensitized solar cells. (October 2015) - Wang, Yun; Sun, Pengfei; Cong, Shan; Zhao, Jie; Zou, Guifu
Abstract: Carbon nanotubes (CNTs) embedding organic ionic plastic crystals electrolytes were prepared and characterized by thermal analysis and scanning electron microscopy to investigate the influence of CNTs contents on the thermal properties and surface morphology. The investigation showed the addition of CNTs had little effect on the melting points and solid–solid phase transition properties of the plastic crystals electrolytes. However, with CNTs increasing, the solid-state electrolytes produced more defected/amorphous regions, resulting in better ionic conductivity and diffusion coefficients of I − and I 3 − . Furthermore, based on these solid-state electrolytes, the resulting solid-state dye-sensitized solar cell exhibited maximal power conversion efficiency of 5.60%, and displayed much more excellent long-term stability than that of referenced ionic liquids-based device. These results offer us a feasible method to develop more excellent plastic crystals electrolytes for high performance solid-state dye-sensitized solar cells.